Parallel paths : the development of nationalism in Ireland and Quebec - Stevenson, Garth, 1943- (Studies in nationalism and ethnic conflict, 2006)
Predominantly Catholic societies subjected to British conquest and partial colonization, Ireland and Quebec rebelled unsuccessfully and entered the modern era with populations divided by language and religion. Ireland failed to achieve home rule within the United Kingdom and chose armed resistance, which led to independence for most of the country at the price of partition. Quebec achieved home rule as a province within the Canadian federation, which led to a century of relative stability followed by the Quiet Revolution and the rise of an independence movement. Almost simultaneously with increased pressure for independence in Quebec, the Irish question erupted again with an armed struggle between supporters and opponents of partition in the six northern counties.